The Deviation Translate of Dutch Translation of the Quran “De Deilige Qoer-an” - Rika Astari; Yusroh Yusroh; Muhammad Irfan Faturrahman (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The Al-Quran translated by De Heilige Qoer-an (DHQ) was a translation of the Qur'an from The Holy Quran, by Maulana Muhammad Ali, the leader and founder of the Ahmadiyya Lahore. The translation of prophetic and miraculous verses shows the occurrence of translation deviations.. This article aims to show the forms of deviations in the translation and interpretation of De Heilige Qoer-an, the factors and the impact of deviations in translation on the context of the meaning of the Qur'an. Material object: in the form of translations of prophetic verses and miraculous verses from the Dutch translation of the Qur'an De Heilige Qoer-an. This research has used a qualitative descriptive approach. The method of data collection is by identifying prophetic verses and miracles of the apostles. Identification is done by comparing the Dutch translation of the Koran with the Indonesian translation of the Koran by H. Fachruddin HS H. Zainuddin Hamidy (1962). Content analysis has been used for data analysis. The translation deviation in DHQ is more caused by lexical translation and the ideology of the translator who translates the Qur'an rationally. The translation of the Qur'anic text based on the translator's ideology has shown a contrast in meaning with the text that corroborates the events of the prophets. Thestudy  provided a new point of view in looking at deviations in the translation of the Qur'anic text, because the existence of text references in other holy books can be a factor causing translation deviations.القرآن الذي كان ترجمته ب De Heilige Qoer-an (DHQ) هو ترجمة للقرآن الكريم الذي كتبه مولانا محمد علي، زعيم ومؤسس الأحمدية لاهور. تظهر ترجمة الآيات النبوية والمعجزية حدوث انحرافات في الترجمة. تهدف هذه المقالة إلى إظهار أشكال الانحرافات في ترجمة وتفسيرDHQ ، وعوامل وتأثير الانحرافات في الترجمة على سياق ترجمة معنى القرآن. مادة البحث: في شكل ترجمات للآيات النبوية والآيات الإعجازية من الترجمة الهولندية للقرآن DHQ، استخدم هذا البحث المنهج الوصفي النوعي. طريقة جمع البيانات هي تحديد الآيات النبوية ومعجزات الرسل. يتم تحديد الهوية من خلال مقارنة الترجمة الهولندية للقرآن بالترجمة الإندونيسية للقرآن بقلم فخر الدين، زين الدين حميد (1962). تم استخدام تحليل المحتوى لتحليل البيانات. إن انحراف الترجمة في DHQ ناتج بشكل أكبر عن الترجمة المعجمية و أيديولوجية المترجم الذي يترجم القرآن بشكل عقلاني. أظهرت ترجمة النص القرآني المستندة إلى أيديولوجية المترجم تباينًا في المعنى مع النص الذي يدعم أحداث الأنبياء. قدم هذا البحث  وجهة نظر جديدة في النظر في الانحرافات في ترجمة النص القرآني، لأن وجود مراجع نصية في الكتب المقدسة الأخرى يمكن أن يكون عاملاً يسبب انحرافات الترجمة.